Hidrogênio como sistema de armazenamento energético de fontes renováveis intermitentes no contexto de uma microrredes - Diaz, Isnel Ubaque (2020)
Hydrogen can be used as an Energy Storage System (ESS), mitigating the intermittency in the supply of electrical energy in a microgrid with high penetration of renewables sources, by allowing that surplus generation can be stored to be used later. Researches have pointed mainly on the design of H2-based components, such as electrolyzer and fuel cell, however few studies have addressed the problem of optimal selection and operation of the set of technologies needed for production, storage and end use of H2. In this work, a model for the optimal selection and operation of Distributed Energy Resources (DERs) is proposed, that allows assessing the feasibility of H2 insertion as an ESS in a microgrid compared to other technologies, taking in account technical, economic and environmental aspects. The optimization model is a mixed-integer linear type, implemented in GAMS, using as input data load profiles of real installation and parameters of commercially available technologies, as well as data of tariff structure currently practiced. The results showed economic and environmental benefits of DERs adoption in a microgrid, compared to the reference scenario where there is not investment and energy demand is entirely supplied by the utility. In the initial tests, the H2 insertion as an ESS showed an improvement in the energy management of intermittent sources, however, the high investment costs make infeasible its insertion in a microgrid, increasing the total annual cost by 2.3 %. When analyzing the impacts of environmental costs, changes in the tariff structure, the greater penetration of renewable generation, and the cost reduction of related technologies to H2 based ESS with the increase of production scale, the insertion of this technology became the best alternative, decreasing the total annual cost by 22.3 %.